Periphery formation and economic-social conflict - Sinóros-Szabó, Botond; Baranyi, Béla (Acta Agraria Debreceniensis, 2013)
The timeliness, significance and importance of the study is sensitively shown by the fact that a large part of the Tisza region is slowly being moved to the periphery in the slowly modernising and changing economic and settlement spatial structure of the Great Plain. This situation is also deepened by the fact that the social and economic backlog increases in the majority of the region, as one third of the 33 most disadvantaged small regions in Hungary can be found here. This study basically contributes to the establishment of the development of the Tisza river’s spatial environment and the development of new solutions.